Al-Quran Literacy on Religious Moderation: Critical Communicative Action Research in IRE Learning in the Digital Era - Ma`arif, Bambang Saiful; Rahmat , Munawar; Suryana, Ermis; ., Tasmuji (Journal of Ecohumanism, 2024)
The Al-Quran is the first and primary reference for Muslims. Even though there is a translation of the Al-Quran, it is challenging for Muslim students to refer directly to the Al-Quran because religious terms are scattered in various surahs and verses, while the Al-Quran is very thick. An instant way is to refer to the website, even though intolerant Salafi-takfiri groups control Islamic social media. As a result, students’ religious thinking is exclusive and intolerant. Digital Quran ver 3.1 is the only digital Quran that is easy, practical, and fun. However, it is difficult for students to learn about and use it. The research aims to increase Al-Quran literacy to increase students’ religious moderation through the CCAR (Critical Communicative Action Research) approach. The research design combines action research steps from Kemmis and McTaggart (planning, acting, evaluating, and reflecting) with Kern’s 3R literacy steps (responding, revising, reflecting). Participants were 400 students from the most significant Islamic University and State University in West Java, Indonesia. Researchers collaborated with IRE lecturers and senior students who mastered the digital Quran ver 3.1 in its implementation. The research found that Al-Quran literacy using the CCAR approach which utilizes digital Quran ver 3.1 is very successful in (1) increasing students’ awareness of the existence and benefits of digital Quran ver 3.1 (from 0% to 100%); (2) increasing students’ skills in installing and applying digital information technology features of the Quran ver 3.1 (from 20.63% to 100%); (3) increasing students’ skills in searching and collecting religious terms from Al-Quran translation applications (from 1.25% to 81.63%); (4) increasing students’ skills in searching and collecting religious terms from Arabic Al-Quran text applications (from 0.5% to 81.63%); and (5) increasing students’ understanding of religious moderation towards non-Muslim perspectives of the Al-Quran (from 22.33% to 78.33%). The implication is that IRE learning needs to optimize the digital Quran ver 3.1 through the CCAR approach to increase students’ religious moderation or to increase their understanding of religion, which aligns with the Al-Quran.